2013
DOI: 10.1007/s00428-013-1500-7
|View full text |Cite
|
Sign up to set email alerts
|

PI3KCA mutation status is of limited prognostic relevance in ER-positive breast cancer patients treated with hormone therapy

Abstract: PI3K/AKT/mTOR pathway alterations are frequent in patients with infiltrating breast cancer (IBC). Their clinical and pathological relevance has been insufficiently documented. We evaluated PI3KCA for mutations and the expression of PTEN, AKT, mTOR and p70S6K by immunohistochemistry in 246 IBC patients treated with hormone therapy (median follow-up, 97 months). A PI3KCA mutation was observed in 50 out of 229 informative cases (21.8 %), PTEN loss in 107 out of 210 (51 %), moderate/high level of expression of AKT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 30 publications
2
17
1
Order By: Relevance
“…Our PIK3CA mutation rate (23.3%) was consistent with the literature, as well as our rate of different hotspot mutations [3,14,19,[22][23][24][25][26][27][28][29][30][31][32][33][34]. Also, we confirmed significant associations of different types of PIK3CA mutations with clinicopathological and molecular characteristics.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our PIK3CA mutation rate (23.3%) was consistent with the literature, as well as our rate of different hotspot mutations [3,14,19,[22][23][24][25][26][27][28][29][30][31][32][33][34]. Also, we confirmed significant associations of different types of PIK3CA mutations with clinicopathological and molecular characteristics.…”
Section: Discussionsupporting
confidence: 91%
“…One important question is the possible effect of PIK3CA status on cancer outcome and treatment efficacy. Notably, many studies examining the prognostic significance of PIK3CA mutations in breast cancer [35] have been published, however very few included a large enough number of patients [3,14,19,[22][23][24][25][26][27][28][29][30][31][32][33][34]. Also, less than half of them [22,24,26,28,30,31,33] used data from clinical trials, thus excluding the effect of treatment heterogeneity when evaluating prognostic factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in the same study, 62.8% of grade 1 carcinomas express p-mTOR (vs 31.9% of grade 2 and 23.4% of grade 3) 7. Furthermore, it was recently demonstrated in patients with locoregional relapse that p-mTOR expression is associated with decreased risk of early relapse, and that high levels of p70S6K (a downstream target of mTORC1), are associated with prolonged OS in lymph node-positive patients 21 22. Others have demonstrated that p-mTOR-expression is more frequent in invasive BCs as compared to carcinoma in situ, or normal breast epithelium,23 yet, based on these results, one cannot assume that the percentage of p-mTOR-expressing tumours will be higher in advanced disease compared to localised invasive disease, or that higher mTOR expression is a surrogate for mTOR pathway activation.…”
Section: Discussionmentioning
confidence: 89%
“…As mentioned above, the published data largely suggest that mutations in PIK3CA occur more frequently in ERC breast cancer with good prognosis and may also be associated with better clinical outcome in patients treated with endocrine therapy (Di Cosimo & Baselga 2009, Miller et al 2011a. However, this is not a universal finding (Cuorvo et al 2014). Recent reviews have discussed this aspect in detail (Fu et al 2013).…”
Section: Introductionmentioning
confidence: 89%